Sustainable business models, venture typologies, and entrepreneurial ecosystems: A social network perspective - Neumeyer, Xaver (2018)
The successful adaptation and creation of sustainable entrepreneurial ventures significantly influences the ability to create more environmentally and socially integrated economic systems. Sustainable business models are a critical component towards this goal. However, the development of sustainable business models is a complex process that requires a supportive entrepreneurial ecosystem. Integrating literature on sustainable business models, network theory, and entrepreneurial ecosystems, we analyze the influence of organizational-level (venture types and venture tenure) and individual-level factors (types of network actors and their demographic characteristics) that influence the social network connectivity of ventures with sustainable and conventional business models. To this purpose, we modeled two municipal entrepreneurial ecosystems in the Southeast United States through a complex network of stakeholders (e.g. entrepreneurs, investors, institutional leaders) and analyzed the resulting social connectivity measures. Our results indicate that sustainable entrepreneurs were underrepresented when compared to conventional entrepreneurs, but that their networks were more densely connected.We also found that different social clusters emerged, based on type of venture and business model, venture tenure, type of network actor (e.g. entrepreneur or investor), or demographic characteristic. With this study, we contribute to the literature on entrepreneurial ecosystems and sustainable business models.